Role of Marine Algal Compounds in Early Brain Development - Padmanabhan, Srihari; Tharan, Ojaswin (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Bioactive substances are related to many benefits regarding health, which include antioxidants, anti-inflammatory, and antimicrobial properties. It is revealed through this research that supplementation of DHA enhances majorly the cognitive development. In studies of animals, the rats are exposed to DHA at the time of lactation, and gestation. On DHA, the major focus presence is noticed in this regard, and on the other side, smaller subsets examine other bioactive compound effects that are found in marine algae. It includes antioxidants and EPA. In the form of primary producers, to the global production of oxygen, the contribution made by them, and also serve in the form of a marine food web foundational components. Despite major findings, in the design of this research the variability, and outcomes emphasize the standard protocols of research requirements. It is reported through many types of research that, the markers are reduced through these compounds of oxidative damage in human trials, and animal models.